Efficiency And Stability Of Islamic Banking In ASEAN - Ahmad Rodoni; Aisyah Raisa Medina; Bahrul Yaman; Sopyan Sopyan (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2020)
This study aims to analyze the efficiency and stability level of Islamic Banking in ASEAN. This study also examins differences in the level of efficiency and stability. Samples used in this study are seven Islamic Banks in five countries in the ASEAN region in 2013-2017. The method used to measure efficiency is Stochastic Frontier Analysis (SFA), while Z-Score is used to measure stability. Tests carried out in this study were hypothesis testing with Binomial Test and Kruskal-Wallis Test. The results indicate that the average efficiency value as a whole is equal to 0,986503. Binomial Test proving that Islamic Banking in ASEAN is efficient and stable. Meanwhile, the average stability value as a whole is 5.21. Furthermore, for the Kruskal-Wallis difference test, it proves that there is no significant difference between the levels of efficiency of Islamic Banking in ASEAN. In contrast, for stability, there is a considerable difference level.Studi ini menanalisis tingkat efisiensi dan stabilitas perbankan syariah di ASEAN. Selain itu, studi ini juga menganalisis perbedaan tingkat efisiensi dan tabilitas. Studi menggunakan sampel 7 bank syariah di 5 negara ASEAN pada periode 2013-2017. Metode yang digunakan untuk mengukur efisiensi adalah Stochastic Frontier Analysis (SFA), sementara untuk stabilitas menggunakan Z-Score. Pengujian yang dilakukan pada studi ini ialah pengujian hipotesis dengan Binomial Test dan Kruskal-Wallis Test. Hasil menunjukkan bahwa rata-rata nilai efisiensi keseluruhan sebesar 0,986503. Binomial Test membuktikan bahwa perbankan syariah di ASEAN efisien dan stabil, sementara itu, nilai rata-rata stabilitas keseluruhan sebesar 5.21. Selanjutnya, untuk uji difference Kruskal-Wallis, mebuktikan bahwa tidak ada perbedaan yang signifikan antara tingkat efisiensi perbankan syariah di ASEAN, sedangkan untuk stabilitas terdapat perbedaan yang signifikan.